2022
DOI: 10.1101/2022.11.22.517556
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deficits in integrative NMDA receptors caused byGrin1disruption can be rescued in adulthood

Abstract: Glutamatergic NMDA receptors (NMDAR) are critical for cognitive function, and their reduced expression leads to intellectual disability. Since subpopulations of NMDARs exist in distinct subcellular environments, their functioning may be unevenly vulnerable to genetic disruption. Here, we investigate synaptic and extrasynaptic NMDARs on the major output neurons of the prefrontal cortex in mice deficient for the obligate NMDAR subunit encoded by Grin1 and wild-type littermates. With whole-cell recording in brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…We therefore performed whole-cell voltage-clamp recordings on second order neurons in lamina 1of the SCDH to determine whether the reduction in NR1 protein levels affected postsynaptic NMDA-evoked current densities. A recent study showed that the synaptic pool of NMDAR was unaffected by a genetic loss of NR1 due to a compensatory shift in NMDAR from extrasynaptic to synaptic sites 33 . Consequently, we chose to bath apply N-Methyl-D-Aspartate (NMDA) followed by washout and found an overall reduction in NMDA-induced currents in dorsal horn neurons (Fig 2D -G).…”
Section: Magi-2 Deficiency Is Associated With Nmdar Hypofunctioningmentioning
confidence: 99%
“…We therefore performed whole-cell voltage-clamp recordings on second order neurons in lamina 1of the SCDH to determine whether the reduction in NR1 protein levels affected postsynaptic NMDA-evoked current densities. A recent study showed that the synaptic pool of NMDAR was unaffected by a genetic loss of NR1 due to a compensatory shift in NMDAR from extrasynaptic to synaptic sites 33 . Consequently, we chose to bath apply N-Methyl-D-Aspartate (NMDA) followed by washout and found an overall reduction in NMDA-induced currents in dorsal horn neurons (Fig 2D -G).…”
Section: Magi-2 Deficiency Is Associated With Nmdar Hypofunctioningmentioning
confidence: 99%